The effect of lactoferrin in aging: role and potential. Issue 2 (20th December 2021) - Li, Bing; Zhang, Bo; Liu, Xudong; Zheng, Yidan; Han, Kuntong; Liu, Henan; Wu, Changjing; Li, Jin; Fan, Shuhua; Peng, Weifeng; Zhang, Fuli; Liu, Xiaomeng
Abstract : The review highlights that LF plays a potential role in aging and longevity of various organisms and modulates major signaling pathways that influence longevity. Abstract : Aging is frequently accompanied by various types of physiological deterioration, which increases the risk of human pathologies. Global public health efforts to increase human lifespan have increasingly focused on lowering the risk of aging-related diseases, such as diabetes, neurodegenerative diseases, cardiovascular disease, and cancers. Dietary intervention is a promising approach to maintaining human health during aging. Lactoferrin (LF) is known for its physiologically pleiotropic properties. Anti-aging interventions of LF have proven to be safe and effective for various pharmacological activities, such as anti-oxidation, anti-cellular senescence, anti-inflammation, and anti-carcinogenic. Moreover, LF has a pivotal role in modulating the major signaling pathways that influence the longevity of organisms. Thus, LF is expected to be able to attenuate the process of aging and greatly ameliorate its effects.